Isolation of Microorganisms from Different College Canteens of Bhilai (Journal of Basic and Applied Research in Biomedicine, 2022)
A food borne diseases are caused by the consumption of contaminated foods. It would seem that a food borne microbial pathogens, microbial toxic product, poisonous chemical causes food borne illness. Many microorganisms present, spoil and contaminate food in home, restaurants, canteens etc. in the present study  bacterial and fungal strains were collected from different college canteens of Bhilai and isolated by various morphological characteristics, biochemical identification etc. Disc diffusion method was used to study antibiotic resistant capability against infectious microorganisms. S. aureus has shown resistance against Amoxicillin, Oxacillin, Ciprofloxin but sensitive to Doxycycline, Erythromycin.  Bacillus subtilis has shown resistant against Oxacilli and Penicilin and Pseudomonas aeruginosa has shown resistant against Gentamycin . Some fungus isolates were also isolated and identified which are harmful to human health. Present study emphasizes presence of microorganism at different sites of college canteens, due to which the society is suffering with serious health hazards. There is need to study more  sites of the city in a future to decrease food contamination, food spoilage and food illness of human being.